Harnessing The Internet for Inclusive Development: Evidence from Spatial Panel Data Analysis in Indonesia - Karmila Maharani; Munawar Ismail; Ferry Prasetyia (Journal of International Conference Proceedings (JICP), 2022)
Technology utilization is often considered one of the main drivers promoting inclusive development. As a form of technology utilization, whether using the internet can promote inclusive development has been a concern for researchers and policymakers. Considering geographical connectivity characteristics, we examine the effects of internet penetration on inclusive development by applying spatial econometric models and using data from 34 provinces in Indonesia from 2015 to 2020. This study reveals that encouraging the internet penetration can significantly improves the inclusive development in a province. However, the increase of internet penetration leads to the decrease of inclusive development in neighboring provinces. The digital divide among provinces in Indonesia can be attributed to this phenomenon. This study also indicates a strong positive spatial correlation of inclusive development. Our findings point to the need for policies to promote people's use of the internet to achieve more benefits from development, balance the digital development to reduce the harmful effects of the digital divide, and consider the spatial aspects when making policies to promote inclusive development.Keywords: Inclusive Development; Internet Penetration; Spatial Analysis